2005
DOI: 10.1007/bf02430258
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrochemical characteristics of 49% PMMA grafted polyisoprene-LiCF3SO3-PC based polymer electrolytes

Abstract: Abstract. Gel polymer electrolytes consisting of 49% PMMA grafted polyisoprene-LiCF3SO3, were plasticized with propylene carbonate (PC) are reported. The effect of PC on the electrochemical properties of the polymer electrolyte has been investigated. Analysis of FTIR spectra shows the interaction of salt and plasticizers with the polymer chain. The ionic conductivity was measured and exhibited a maximum value of 104 S/cm. The temperature dependence of the electrical conductivity follows the Arrhenius law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
3
22
0
Order By: Relevance
“…With the addition of lithium salt, a new band evolves at the lower frequency side which is at 1,715 cm −1 . The shift of C=O symmetric stretching of MMA peak confirmed the interaction between lithium ions from doping salt and oxygen atoms in the structure of the polymer host to form a coordinate bond and subsequently forming polymer-salt complexes, which is in a good agreement with a previous report [3,4,15,17,18]. The C=O symmetric stretching of MMA peaks is shifted to a lower wave number at 1,712 cm −1 and becomes less intense as the EC content increases.…”
Section: Ftir Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…With the addition of lithium salt, a new band evolves at the lower frequency side which is at 1,715 cm −1 . The shift of C=O symmetric stretching of MMA peak confirmed the interaction between lithium ions from doping salt and oxygen atoms in the structure of the polymer host to form a coordinate bond and subsequently forming polymer-salt complexes, which is in a good agreement with a previous report [3,4,15,17,18]. The C=O symmetric stretching of MMA peaks is shifted to a lower wave number at 1,712 cm −1 and becomes less intense as the EC content increases.…”
Section: Ftir Studiessupporting
confidence: 89%
“…The main focus of this FTIR is in the region of the carbonyl group (C=O) (1,750-1,730 cm −1 ) and ether group (C-O-C) (1,300-1,000 cm −1 ) in MG49 [4,17]. According to the previous report, the ester functional group in MMA appears through a strong and sharp peak of C=O in the range of 1,750-1,735 cm −1 which shift to a lower wave number by about 15-25 cm −1 in the polymer-salt complexes [5,17,18]; however, a very strong, intense and sharp peak at 1,726 cm −1 in Fig. 2a corresponding to the C=O symmetrical stretching frequency of MG49.…”
Section: Ftir Studiesmentioning
confidence: 99%
“…Furthermore, modified natural rubber such as 49% grafted poly(methyl methacrylate) (MG49) with its structure shown in Fig. 2 have a polar group in their carbonyl functional group that will provide coordination sites for Li + conduction [18][19][20][21][22][23]. In addition, the use of modified natural rubber will produce the electrolyte that is low in cost and environmental friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, rubber polymer electrolytes had drawn the attention of many researchers [3][4][5][6][7][8][9]. Modified natural rubber has attractive attributes; it is free standing, flexible and has good elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the oxygen atoms and lithium ions of the metal salt forms a coordinate bond and generates polymer-salt complexes [5,6]. Previous studies on various MG were reported elsewhere [5,7,8]. However, MG based polymer electrolytes without plasticizers such as polypropylene carbonate (PC) and ethylene carbonate (EC) provide low ionic conductivity values.…”
Section: Introductionmentioning
confidence: 99%